The Status, Habitat and Nest of the Satanic Nightjar Eurostopodus diabolicus - Jon Riley; James C Wardill (Indonesian Ornithologists’ Union, 2003)
The Satanic Nightjar Eurostopodus diabolicus a little-known, putatively threatened species endemic to Sulawesi, Indonesia was recently observed in two protected areas in North Sulawesi. Presently classified as Vulnerable to extinction, these new records suggest a more widespread geographical distribution and greater tolerance of disturbed habitats than was previously thought. Consequently, we recommend that this species be downgraded to Near Threatened. Descriptions of plumage characters (which differ from the type specimen in some respects), nesting, and behaviour are presented. Morphological and ecological evidence suggests E. diabolicus is most closely related to the Archbold's Nightjar E. archboldi and Papuan Nightjar E. papuensis, both endemic to New Guinea.